Improving The Cognitive Development Of 5-6 Year-Old Children By Using Outbound Activities At Anak Ceria Tembobor Kindergarten In The 2024/2025 Academic Year - Siti Hajar; Marzoan Marzoan; Juandra Primsa Mahendra (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to improve the cognitive development of children aged 5-6 years at TK Anak Ceria Tembobor. The number of subjects was 20 children. This research is a class action research. The data that has been collected is analyzed by observation, interview and documentation techniques, using classical and personal / individual completeness formulas. The result of this study is that using outbound activities can improve the cognitive development of children aged 5-6 years at Anak Ceria Tembobor Kindergarten. This is evidenced by the cognitive improvement data obtained by children has increased, starting from the data before the implementation of the action until the implementation of cycle II action. Before the implementation of the completed as many as 2 people with a percentage of 20%. in cycle I got a complete child, namely 5 children with a percentage of 50%. and at the end of cycle II action obtained significant action, namely 9 children with a percentage of 90% cognitive improvement. The type of research used is Classroom Action Research. Classroom action research is defined as a practical research to improve learning in the classroom, by taking action to find solutions to problems faced daily in the classroom. So that in essence the implementation of class action research is carried out in order for teachers to be willing to introspect, reflect, reflect or evaluate themselves on their own. Keywords: Cognitive, Outbound activities, Early Childhood